Detection of the bcl-2 t(14;18) Translocation and Proto-Oncogene Expression in Primary Intraocular Lymphoma - Wallace, Dana J. (2006)
PURPOSE: Primary intraocular lymphoma (PIOL) is a diffuse large B cell lymphoma that initially infiltrates the retina, vitreous, or optic nerve head, with or without central nervous system involvement. This study examined the expression of the bcl-2 t(14;18) translocation, the bcl-10 gene, and high expression of bcl-6 mRNA in PIOL cells. METHODS: Microdissection and PCR analysis were used to examine vitreous specimens in patients with PIOL for the presence of bcl-2 t(14;18) translocations, the bcl-10 gene, and expression of bcl-6 mRNA. A medical record review was also conducted to determine whether the bcl-2 t(14;18) translocation correlated with prognosis. RESULTS: Forty of 72 (55%) PIOL patients expressed the bcl-2 t(14;18) translocation at the major breakpoint region. Fifteen of 68 (22%) patients expressed the translocation at the minor cluster region. The bcl-10 gene was detected in 6 of 26 (23%) patients, whereas 4 of 4 (100%) PIOL patients expressed higher levels of bcl-6 mRNA compared with inflammatory lymphocytes. An analysis of clinical outcome in 23 PIOL patients revealed no significant association between bcl-2 t(14;18) translocations and survival or relapse. However, patients with the translocation were significantly younger. CONCLUSIONS: PIOL has unique molecular patterns of bcl-2, bcl-10, and bcl-6 when compared with other systemic lympho-mas. This study lays the foundation for future studies aimed at exploring the genotypic classification of PIOL based on the quantitative molecular framework of gene expression profil-ing, with the goal of providing useful adjuncts to the pathologic diagnosis of this complex disease.